2023
DOI: 10.3892/etm.2023.11832
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‑related parameters as potential biomarkers for the prognosis of sepsis

Abstract: Early diagnosis and accurate prognosis are key for reducing the fatality rate and medical expenses associated with sepsis. Platelets are involved in the delayed tissue injury that occurs during sepsis. Therefore, the aim of the present study was to investigate the usefulness of platelets and associated parameters as prognostic markers of sepsis. The present study collected patient samples based on The Third International Consensus Definitions for Sepsis and Septic Shock criteria. Platelet-associated parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Identifying potential prognostic biomarkers is essential for the prognosis and treatment of sepsis. The number and function of platelets can reflect the severity of sepsis and are closely related to patient prognosis [18,19]. We screened 10 PRGs associated with the prognosis of sepsis patients, established a prognostic risks core model, and developed a nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying potential prognostic biomarkers is essential for the prognosis and treatment of sepsis. The number and function of platelets can reflect the severity of sepsis and are closely related to patient prognosis [18,19]. We screened 10 PRGs associated with the prognosis of sepsis patients, established a prognostic risks core model, and developed a nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, platelets play a vital role in immune response, pathogen clearance, tissue repair, hemostasis, and thrombosis. Platelet-related parameters have proven useful in predicting the prognosis and mortality of sepsis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al [ 30 ] conducted a study on the diagnosis of sepsis using multiple biomarkers, which showed that combining any 2 biomarkers can improve the sensitivity and specificity of sepsis diagnosis. The ROC curve analysis in this study showed that the AUC for PCT and PLT in predicting patient prognosis was 0.808 (95% CI: 0.733–0.882) and 0.804 (95% CI: 0.746–0.861), respectively, with both P values <.001.…”
Section: Discussionmentioning
confidence: 99%